Ecological effects of interplanted sweet alyssum and alfalfa in an organic day-neutral strawberry production system - Gullickson, Matthew G.; Suresh, Jayanti; Hegeman, Adrian D.; Rogers, Mary A. (Frontiers in Ecology and Evolution, 2025)
Production of day-neutral strawberries (Fragaria x ananassa) is increasing in the Upper Midwest region of the USA, resulting in an extended strawberry harvest season compared to traditional June-bearing production systems. However, the longer harvest season comes with additional insect pest pressure and the need for novel integrated pest management strategies. Spotted-wing drosophila (Drosophila suzukii; SWD) and tarnished plant bug (Lygus lineolaris; TPB) can decrease strawberry yield and fruit quality. Insecticides are the dominant management strategy for both insect pests; however, fewer effective insecticides are available in organic production systems. Interplanting is an integrated pest management strategy which can provide conservation biological control and may repel or attract species of interest through volatile organic compound (VOCs) emissions. We investigated the effect of interplanting alfalfa and sweet alyssum with day-neutral strawberry plants on fruit yield and quality, SWD infestation and TPB damage, arthropod abundance and diversity. Additionally, we measured the relative abundance of sweet alyssum VOCs, acetophenone and benzaldehyde, in the field because they may be aversive to SWD adults. The interplanting treatment inconsistently affected fruit production; in year one of the study, the control treatment had larger fruit than the other two treatments and, in year two, berries interplanted with sweet alyssum had more marketable yield than the other two treatments. Treatments did not affect SWD infestation or TPB damage. Acetophenone and benzaldehyde VOC production varied in the sweet alyssum plots by time of day and date. The control treatment had less arthropod abundance and diversity compared to the intercrop treatments. Intercropping may provide resources for arthropod communities but may not reduce key pest species such as SWD and TPB in day-neutral strawberries.